Electrochemical investigation and stripping voltammetric determination of captopril at CuO nanoparticles/multi-wall carbon nanotube nanocomposite electrode in tablet and urine samples. Issue 3 (16th December 2014) - Zargar, Behrooz; Parham, Hooshang; Hatamie, Amir
Abstract : Determinations of captopril were made using a nanocomposite electrode modified with CuO nanoparticles (CuO NPs) and multiwall carbon nanotubes (MWCNTs). Abstract : Determinations of captopril were made using a nanocomposite electrode modified with CuO nanoparticles (CuO NPs) and multiwall carbon nanotubes (MWCNTs). The voltammetric results indicate that MWCNT can remarkably enhance electrocatalytic activity toward the oxidation of captopril in buffer solution. Characteristics of the electrochemical responses of the modified electrode toward captopril were investigated by cyclic voltammetry (CV), differential pulse voltammetry (DPV) and chronoamperometry. The parameters of charge transfer rate constant ( k s ), charge transfer coefficient ( α ), diffusion coefficient ( D ), electrode surface area ( A ), and catalytic rate constant ( k h ) were determined, and the results were investigated. The electrocatalytic oxidation current of captopril was found to have a linear relation to concentration over the range 4.6 × 10 −7 M–1 × 10 −5 M ( n = 7) determined by the DPASV method. The limit of detection at S / N ratio of 3 was 2.9 × 10 −7 M ( n = 6), and the relative standard deviation was 4.4% at the 4 × 10 −6 M level ( n = 6). The prepared modified electrode has the advantages of high sensitivity, low detection limit in comparison with some reported methods, simple preparation and regeneration of the electrode surface by simple polishing that enables acceptable reproducibility. The modified electrode can be applied to determine captopril in tablets and urine samples with satisfactory results.